Development of Learning Materials and Media for Vocational Competency Basic Subjects in Class X Audio Video Engineering in SMK Negeri 2 Samarinda - Sinambela, Nurasi (Educationist: Journal of Educational and Cultural Studies, 2022)
The aim of this research are: (1) to produce learning materials and media for vocational basic competence, (2) to know teachers responses of produced learning materials and media, and (3) to know students responses of produced learning materials and media. The method used in this research is Research and Development method with 7 stages, namely: (1) potential and problem, (2) information collecting, (3) product design, (4) validated design, (5) product revision, (6) implementation of product, and (7) analysis and reporting. The subject of this research are year X TAV1 students at SMK Negeri 2 Samarinda. The product from this research is learning materials and media for vocational basic competence with standard competence make of audio recording in studio of include basic competence namely: (1) explain the process of duplication, (2) operated recording instrument, and (3) take care of recording instrument. The result of teacher questioner show that the percentage of teacher responses is 76,67%, it means that the learning materials and media was good to be used by teacher for teaching learning material. The result of student questioner show that the percentage of student responses is 85,12%, it means that the learning materials and media was very good to help student to understand the learning materials.